Terminal Ileal Perforation due to Various Etiologies and their Treatment Modalities (Medical Forum Monthly, 2024)
Background: Terminal ileum perforation is quite common in developing countries carrying high morbidity and mortality.Study Design: Retrospective case studyPlace and Duration of Study: This study was carried out at the Department of General Surgery, Allama Iqbal Memorial Hospital, Sialkot from March 2007 to March 2013.Materials and Methods: The study was aimed to find aetiological factors of Terminal ileum perforation and different treatment modalities for such perforation.Results: There were 34 typhoid, 6 tuberculous, 14 non-specific and 2 others of foreign body and ascariasis. Various surgical procedures like Covering ileostomy, Closure with exteriorization, Ileostomy alone, Resection of perforation with covering ileostomy and Right hemicolectomy were done depending upon the severity of disease and clinical status of the patient.Conclusion: Treatment of Terminal ileal perforation is always surgical regardless of the techniques. Operation must be done as soon as possible and should be associated with aggressive resuscitation before operation. This results in remarkable decrease in morbidity and mortality of the patients. Response of treatment modalities varies from patient to patient depending upon the aetiological factors. The outcome is very encouraging in those who present earlier.